2013
DOI: 10.1152/japplphysiol.01132.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan initiates chondrogenesis mainly via CD44 in human adipose-derived stem cells

Abstract: Cell-matrix adhesion is one of the important interactions that regulates stem cell survival, self-renewal, and differentiation. Our previous report (Wu SC, Chang JK, Wang CK, Wang GJ, Ho ML. Biomaterials 31: 631-640, 2010) indicated that a microenvironment enriched with hyaluronan (HA) initiated and enhanced chondrogenesis in human adipose-derived stem cells (hADSCs). We further hypothesize that HA-induced chondrogenesis in hADSCs is mainly due to the interaction of HA and CD44 (HA-CD44), a cell surface recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 47 publications
3
70
0
1
Order By: Relevance
“…5,51,52 A previous study has shown that signaling triggered by binding of CD44 to HA is important for chondrogenesis as blocking with anti-CD44 antibodies inhibited chondrogenesis in adipose-derived stem cells. 53 Thus, the increased membrane-localized CD44 staining in cells on PEG-GelMA-HA scaffolds may indicate that CD44 is binding to HA and this binding triggers signaling for chondrogenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…5,51,52 A previous study has shown that signaling triggered by binding of CD44 to HA is important for chondrogenesis as blocking with anti-CD44 antibodies inhibited chondrogenesis in adipose-derived stem cells. 53 Thus, the increased membrane-localized CD44 staining in cells on PEG-GelMA-HA scaffolds may indicate that CD44 is binding to HA and this binding triggers signaling for chondrogenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…Among natural polymer hydrogels for tissue‐engineered cartilage development are collagen I and II, hyaluronan, fibrin glue, alginate, chitosan, gelatin etc . A quantitative in vitro accumulation of the cartilage matrix has been demonstrated histologically, immunohistochemically, and biochemically for chondrocytes and MSCs from different sources, cultured in collagen, hyaluronan, chitosan, alginate, fibrin, and self‐assembling peptides . Most of these matrices also support neocartilage matrix deposition in vivo when implanted into nude mice …”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that human adipose‐derived mesenchymal stromal cells (hADSCs) are adhesive, have a fibroblast‐like morphology, express multiple CD marker antigens satisfying MSCs phenotype and possess multilineage potential to differentiate in mesenchymal lineages . Several previous studies have shown that hADSCs undergo chondrogenesis and deposit a cartilage‐specific matrix in pellet cultures and in a variety of natural and synthetic scaffold materials in the presence of the appropriate growth factors …”
Section: Introductionmentioning
confidence: 99%
“…Since CD44 is overexpressed in tumor cells and plays a key role in metastasis, targeting CD44 with HA-covered particles has demonstrated a great potential to improve drug delivery [13]. CD44 is also expressed in articular cells and involved in matrix attachment and signal transduction [14,15]. HA is a major component of extracellular matrix and synovial fluid and is internalized by chondrocytes through CD44 binding [16].…”
Section: Introductionmentioning
confidence: 99%